2000
DOI: 10.1074/jbc.275.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Escherichia coliGlucosamine-6-phosphate Synthase by Reactive Intermediate Analogues

Abstract: Glucosamine-6-phosphate synthase (GlmS) catalyzes the formation of D-glucosamine 6-phosphate from D-fructose 6-phosphate using L-glutamine as the ammonia source. Because N-acetylglucosamine is an essential building block of both bacterial cell walls and fungal cell wall chitin, the enzyme is a potential target for antibacterial and antifungal agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 57 publications
(44 reference statements)
0
29
0
1
Order By: Relevance
“…Other glutamine analogues with low micromolar K i values have been synthesized, such as the γ‐dimethylsulfonium derivative (Walker et al , 2000). Some carbohydrate compounds, like 2‐amino‐2‐deoxy‐ d ‐glucitol‐6‐phosphate, have been shown to inhibit the enzyme competitively with respect to fructose‐6‐phosphate (Badet‐Denisot et al , 1995); recently, other carbohydrate‐based inhibitors have been designed as analogues of the reaction intermediates (Bearne & Blouin, 2000). N ‐iodoacetylglucosamine‐6‐phosphate is an active site‐directed irreversible inactivator of GlmS from Escherichia coli , and it interacts with both the sugar‐ and the glucosamine‐binding sites (Bearne, 1996).…”
Section: Biosynthesis Of Udp‐n‐acetylglucosaminementioning
confidence: 99%
“…Other glutamine analogues with low micromolar K i values have been synthesized, such as the γ‐dimethylsulfonium derivative (Walker et al , 2000). Some carbohydrate compounds, like 2‐amino‐2‐deoxy‐ d ‐glucitol‐6‐phosphate, have been shown to inhibit the enzyme competitively with respect to fructose‐6‐phosphate (Badet‐Denisot et al , 1995); recently, other carbohydrate‐based inhibitors have been designed as analogues of the reaction intermediates (Bearne & Blouin, 2000). N ‐iodoacetylglucosamine‐6‐phosphate is an active site‐directed irreversible inactivator of GlmS from Escherichia coli , and it interacts with both the sugar‐ and the glucosamine‐binding sites (Bearne, 1996).…”
Section: Biosynthesis Of Udp‐n‐acetylglucosaminementioning
confidence: 99%
“…Investigations of the docked conformations of GlcN-6-PS and oxasetin revealed that the NH group at position-1 and the carbonyl group at position-5 of the pyrrole-2,5-dione ring provide sites for receptor interaction by donating and accepting a hydrogen bond with Glu-488 and Ser-401 residues, respectively. Data from the literature also support the amino function as an important moiety to be included in the design of GlcN-6-PS inhibitors [22]. The carbonyl group that connects the octahydronaphthalene and pyrrole-2,5-dione rings of the oxasetin molecule also seems to be important for the binding interaction, as it accepts two hydrogen bonds, each from Thr-302 and Ser-303 ( Figure 5).…”
mentioning
confidence: 90%
“…The extensive literature survey and the continuous attempt of our group for exploring novel antimicrobial and antioxidant agents encourages us to synthesize novel series of 2-pyrazoline derivatives containing imine (Schiff base) moiety. The target compounds (3)(4)(5)(6)(7)(8)(9) were prepared and screened against several bacterial species (gram positive and gram negative) and also against Candida albicans. The antioxidant activity of the synthesized derivatives against 2,2-diphenyl-l-picrylhydrazyl (DPPH) radical by the TLC autographic and quantitatively by spectrophotometric assay was achieved.…”
Section: Introductionmentioning
confidence: 99%